Morphometric and histological changes in cardiac nodes after acute spontaneous myocardial infarction in humans and pigs - Fabián Gómez-Torres; Luis Ernesto Ballesteros-Acuña; Pilar Molina-Aguilar; César Ríos-Navarro; Amparo Ruíz-Sauri (Veterinary World)
Background and Aim: The sinoatrial node is responsible for the intrinsic electrical activation that in mammals leads to coordinated rhythmic contractions of the heart, from where it is distributed through the atrial tissue to the atrioventricular node. This study aimed to conduct a histological and morphometric study of the components and cells in cardiac nodes altered by myocardial infarction (MI) and compare them with normal tissues in humans and pigs.